The Role of Anterior Nuclei of the Thalamus: A Subcortical Gate in Memory Processing: An Intracerebral Recording Study - Štillová, Klára; Jurák, Pavel; Chládek, Jan; Chrastina, Jan; Halámek, Josef; Bočková, Martina; Goldemundová, Sabina; Říha, Ivo; Rektor, Ivan (PloS one, 2015)
OBJECTIVE: To study the involvement of the anterior nuclei of the thalamus (ANT) as compared to the involvement of the hippocampus in the processes of encoding and recognition during visual and verbal memory tasks. METHODS: We studied intracerebral recordings in patients with pharmacoresistent epilepsy who underwent deep brain stimulation (DBS) of the ANT with depth electrodes implanted bilaterally in the ANT and compared the results with epilepsy surgery candidates with depth electrodes implanted bilaterally in the hippocampus. We recorded the event-related potentials (ERPs) elicited by the visual and verbal memory encoding and recognition tasks. RESULTS: P300-like potentials were recorded in the hippocampus by visual and verbal memory encoding and recognition tasks and in the ANT by the visual encoding and visual and verbal recognition tasks. No significant ERPs were recorded during the verbal encoding task in the ANT. In the visual and verbal recognition tasks, the P300-like potentials in the ANT preceded the P300-like potentials in the hippocampus. CONCLUSIONS: The ANT is a structure in the memory pathway that processes memory information before the hippocampus. We suggest that the ANT has a specific role in memory processes, especially memory recognition, and that memory disturbance should be considered in patients with ANT-DBS and in patients with ANT lesions. ANT is well positioned to serve as a subcortical gate for memory processing in cortical structures.
Keywords: evokované potenciály; Adult; lidé středního věku; hipokampus; Electrodes, Implanted; nuclei anteriores thalami; ženské pohlaví; Epilepsy; hluboká mozková stimulace; Anterior Thalamic Nuclei; lidé; Memory; Electroencephalography; mužské pohlaví; Deep Brain Stimulation; Evoked Potentials; dospělí; paměť; implantované elektrody; Humans; Hippocampus; Female; elektroencefalografie; epilepsie; Middle Aged; Male